2014
DOI: 10.1111/cpf.12131
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide after high‐intensity exercise at 2800 m altitude

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Stang, J., Bråten, V., Caspersen, C., Thorsen, E., Stensrud, T. (2014 1 ABSTRACT Background: Nitric oxide (NO) concentration in exhaled gas is a marker of some inflammatory processes in the lung and endogenous NO plays a role in the physiological responses to exercise and altitude. The aim of this study was to compare changes in exhaled NO concentration 5-60 min after high intensity exercise at 2800 m and at 180 m altitude. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…Data suggest that NO content is decreased in the exhaled air from the volunteers after running on a treadmill at altitudes of 2800 and 180 m for several minutes. Partial pressure of NO significantly decreases at both altitudes (Stang et al, 2014 ). What are the factors limiting NO signaling?…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that NO content is decreased in the exhaled air from the volunteers after running on a treadmill at altitudes of 2800 and 180 m for several minutes. Partial pressure of NO significantly decreases at both altitudes (Stang et al, 2014 ). What are the factors limiting NO signaling?…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a larger study aiming to assess the effect of different environments including altitude (Stang et al ., ) upon FE NO .…”
Section: Methodsmentioning
confidence: 98%
“…Several studies, including clinical trials, have shown that aerobic exercise produces anti-inflammatory and antioxidant effects in different diseases, such as heart disease [ 25 ], diabetes [ 26 ], Alzheimer’s disease [ 27 ], and Parkinson’s disease [ 28 ], as well as in lung diseases, such as COPD [ 29 31 ], ARDS [ 32 , 33 ] and asthma [ 34 38 ]. Notably, Vieira et al, (2011) showed that aerobic exercise at low and moderate intensities resulted in the immunomodulation of epithelial cells from the airway of animals with long-term allergic lung inflammation, thus decreasing the oxidative stress and lung inflammation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Camiletti-Moirón et al (2013) demonstrated a deteriorated antioxidant response in the brains of rats trained using high-intensity aerobic exercise [ 42 ]. Regarding lung effects, specifically, Stang et al (2014), showed that after high-intensity exercise, there is a significant reduction in exhaled nitric oxide concentration, known by its inflammatory role into the lungs [ 31 ]. These studies highlighted the anti-inflammatory and pro-inflammatory response, as well as the changes in redox balance, induced by high-intensity aerobic exercise [ 40 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation